Da decisão por equidade na arbitragem internacional - Romanelli, Rafaella Midori Shikida de Parcibale (2023)
This project seeks to analyze the institute of arbitration in equity, as well as the meaning of the term itself, with the analysis of doctrinal texts to understand the historical, legal, and social importance of the equity judgment in international arbitrations, and its effects in the civil sphere and legal, detailing its application, more specifically, in the world of international arbitration. In this sense, the point is to analyze the limits of such an institute as an arbitrator's tool for resolving conflicts, in the search for achieving a fairer and more inclusive resolution for the parties involved in the conflict. Finally, there will be an analysis of concrete cases in the use of equity by international bodies, in its concept and form, as well as its legal effects for the agreed parties